2005
DOI: 10.1016/j.visres.2005.07.041
|View full text |Cite
|
Sign up to set email alerts
|

The role of attention in binding shape to color

Abstract: Pictures of easily-identifiable objects with novel colors (e.g. a blue frog) or of forms with arbitrary colors (e.g. a green triangle) were presented briefly at 10.6 degrees eccentricity. Stimuli had strong outlines and vivid fill colors (red, green, yellow, blue, or purple). The same pictures were repeated once in each block of 30 trials for 6, 9, or 12 blocks, and recognition was probed after each block. Shapes were acquired quickly, within 3-4 blocks, whether attention was focused on the pictures or split t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Moreover, as participants were instructed to maintain fixation on the cross throughout the experiment, foveal (i.e., color) vision was relatively less engaged by the stimuli. While our use of grayscale images differs from previous addiction-related AB studies, this experimental design is in keeping with the broader field of visual attention (e.g., O'Craven et al 1999; Corbetta et al 2005; Bar et al 2006), in which color images are more rarely employed unless the effects of color are specifically under investigation (e.g., Bonnel and Prinzmetal 1998; Reeves et al 2005). The maintenance of central fixation means that we were exploring covert attentional orienting, although covert effects are comparable to overt attention effects (Bradley et al 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, as participants were instructed to maintain fixation on the cross throughout the experiment, foveal (i.e., color) vision was relatively less engaged by the stimuli. While our use of grayscale images differs from previous addiction-related AB studies, this experimental design is in keeping with the broader field of visual attention (e.g., O'Craven et al 1999; Corbetta et al 2005; Bar et al 2006), in which color images are more rarely employed unless the effects of color are specifically under investigation (e.g., Bonnel and Prinzmetal 1998; Reeves et al 2005). The maintenance of central fixation means that we were exploring covert attentional orienting, although covert effects are comparable to overt attention effects (Bradley et al 2000).…”
Section: Methodsmentioning
confidence: 99%
“…This result seems to be very general. In particular, authors in [56] have suggested that attention facilitates the creation and maintenance of novel color-shape bindings in the visual periphery; without attention, binding is less effective.…”
Section: Resultsmentioning
confidence: 99%
“…3). Studies have shown that, in the absence of other visual information, it is easy for human beings to identify objects by shape [43][44][45] . Adults and children prefer to categorize novel objects according to shapes, given con icting colors and texture cues.…”
Section: Discussionmentioning
confidence: 99%
“…Adults and children prefer to categorize novel objects according to shapes, given con icting colors and texture cues. Shape features play a more important role in inductive reasoning than do color features 44,45 . Shape similarity is the rst strategy used in inductive reasoning in early childhood 46 .…”
Section: Discussionmentioning
confidence: 99%